Suppressed Inflation and Money Demand in Zimbabwe - Munoz, Sonia (IMF Working Papers; Working Paper ;, 2006)
The paper investigates the divergence between inflation and monetary expansion in Zimbabwe since late 2003. The substantial decline in velocity and increasing levels of real money balances during 2004 are at odds with a record of inflation closely tracking the growth rates of monetary aggregates in the past. Possible explanations for the divergence include an unstable demand for money, a sudden shift in the underlying demand for real balances due to a sharp change in an explanatory variable, and a structural break or aberration in a normally stable money demand relation reflecting some unexplained factor such as repressed inflation (given administered prices) or measurement errors in the consumer price index. The results of the study point to the last possibility as the most likely explanation.